Clinical severity and patterns of organ involvement in acute systemic lupus erythematosus flares and predictors of disease severity: a retrospective study - Shivam; Panigrahy, Gyanamitra; Sengupta, Piyali; Singh, Shashi; M. Babu, Challagulla; Goyal, Dipleshdeep; S. Srinivas, Miriyala; Mohanty, Lalatendu (International Journal of Research in Medical Sciences, 2025)
Background: Acute, severe flares of systemic lupus erythematosus (SLE) are associated with significant morbidity and mortality, yet robust, accessible predictors for poor outcomes are not fully established. We aimed to identify the clinical and laboratory characteristics associated with in-hospital mortality in patients with severe SLE flares. Methods: We conducted a retrospective, cross-sectional study of 30 adult patients admitted for a severe SLE flare (SLE disease activity index 2000 [SLEDAI-2K] score >6) to a tertiary care center in Bhubaneswar, India, between January 2024 and January 2025. We extracted demographic, clinical, and comprehensive laboratory data. Pearson’s correlation was used to assess the relationship between SLEDAI-2K and laboratory parameters. Baseline characteristics were compared between survivors and non-survivors to identify predictors of the primary outcome, in-hospital mortality. Results: The cohort was predominantly female (80.0%) with a median age of 28 years and high disease activity at admission (median SLEDAI-2K, 17.5). The overall in-hospital mortality rate was 13.3% (4 of 30). Disease activity strongly correlated with red cell distribution width (r=0.892), anti-dsDNA levels (r=0.760), complement C3 (r=–0.846), and mean platelet volume (r=–0.820; all p<0.001). Compared to survivors, non-survivors had significantly higher median SLEDAI-2K scores (29.0 versus 16.0, p<0.001) and a higher frequency of neurological involvement (75.0% versus 15.4%, p=0.025). Severe leukopenia (median WBC 1.8 versus 7.2×103/μl, p<0.001) and thrombocytopenia (median platelets 42.5 versus 172.0×103/μl, p=0.005) were also significantly associated with mortality. Conclusions: In patients hospitalized for severe SLE flares, high baseline disease activity, neurological involvement, and profound cytopenias are key predictors of in-hospital mortality. Readily available hematological indices, particularly RDW and MPV, correlate strongly with disease activity and may serve as useful adjuncts for risk stratification.